Optimization of n-hexane reforming using taguchi orthogonal Array Design - Chandra Mohan Sinnathambi,; Reem Ahmed Mohammed Ismail, (Universiti Kebangsaan Malaysia, 2012)
Taguchi orthogonal array design, a statistical software is applied to n-hexane reforming. The purpose is to identify the most significant process variable in reforming conditions favouring n-hexane conversion to high aromatics and isomers and low cracked and coke precursor reformate products. Actual experimental data were used for this study. Three process variables i.e. temperature, contact time and hydrogen partial pressure were investigated. From the study it was found that the contact time was the most critical operating parameter for n-hexane conversion followed by reaction temperature and hydrogen partial pressure. It was also noted that enhanced n-hexane reforming conversion can be achieved by operating the process at reaction temperature 723 K and contact time 7.1 min with a H2 partial pressure 300 kPa. For selectivity to aromatics and isomers lower contact time of 1.07 min with intermediate hydrogen partial pressure of 300 to 500 kPa operating at a reaction temperature of 723 K is most favourable.